Impact of Continuous Assessment on Pupils’ Academic Performance in Primary Schools in Kabale Municipality, Kabale District - Asaph, Aturinzire (Kabale University, 2022)
A Dissertation Submitted to the Directorate of Postgraduate training in Partial Fulfilment of the Requirements for the Award of a Degree of Master of Arts in Education Management of Kabale University